Anxiety level measured at term pregnant with scale questionnaire Hamilton (HAM-A) based on factor characteristics - Bandini dr; Nazarudin Jaffar; Sarma N Lumbanraja; Ahmad Khuwailid; Indra Z Hasibuan; M. Oky Prabudi (Majalah Kedokteran Nusantara The Journal Of Medical School, 2014)
Background : Psychological changes that occur during pregnancy can alter behavior during and after childbirth. Throughout pregnancy, especially near term, raised concerns about child care and lifestyle changes. The conflict between the desire of procreation, social norms and cultural problems in the pregnancy itself can be an originator of a variety of psychological reactions, ranging from mild emotional reaction to the rate of mental disorders. Pregnancy and childbirth have safety risks that will affect the level of maternal anxiety during pregnancy and before delivery. So which is the formulation of the problem in this research is how the characteristics of pregnant women at term factor affecting the level of anxiety.Methods : The subjects were patients at the outpatient clinic of Obstetrics and gynecology Dr Haji Adam Malik, and hospital networks. the way of sampling through consecutive sampling with criteria for inclusion and exclusion to a minimum sample size of each group 55 samples. using bivariate data analysis with comparative analytic using Chi Square test for categorical variables and independent t-test for numerical variables.Results : Pregnant women who give birth either spontaneous vaginal delivery (87.3%) as well as a Cesarean section (87.3%) did not feel anxious. mild anxiety pregnant women who will give birth to spontaneous delivery (12.7%) and cesarean section (12.7%). Statistically with Chi-square test showed no significant difference.Conclusion : Conclusion pregnant women who planned spontaneous vaginal delivery or cesarean section does not feel any anxiety in the face of labor .Keywords : anxiety; pregnancy; spontaneous vaginal delivery; cesarian section